The CBD Post‐2020 biodiversity framework: People's place within the rest of nature. Issue 6 (6th October 2022) - Friedman, Kim; Bridgewater, Peter; Agostini, Vera; Agardy, Tundi; Arico, Salvatore; Biermann, Frank; Brown, Kate; Cresswell, Ian D.; Ellis, Erle C.; Failler, Pierre; Kim, Rakhyun E.; Pratt, Christelle; et al.
Abstract: Recognizing two decades of failure to achieve global goals and targets, parties to the Convention on Biological Diversity are in the final phase of negotiating a Post‐2020 Global Biodiversity Framework for the conservation, sustainable use and benefit sharing of biodiversity. The framework attempts to set out pathways, goals and targets for the next decade to achieve positive biodiversity change. This perspective intends to help that framework set people firmly as part of nature, not apart from it. Despite work done so far through four meetings, new thinking and focus is still needed on 'what' changes must be conceptualized and implemented, and 'how' those changes are to be delivered. To help achieve that new thinking, as a broad range of people, many with a focus on aquatic systems, we highlight six key foci that offer potential to strengthen delivery of the framework and break the 'business as usual' logjam. These foci are as follows: (i) a reframing of the narrative of 'people's relationship with the rest of nature' and emphasize the crucial role of Indigenous Peoples and Local Communities in delivering positive biodiversity change; (ii) moving beyond a focus on species and places by prioritizing ecosystem function and resilience; (iii) supporting a diversity of top‐down and bottom‐up governance processes; (iv) embracing new technologies to make and measure progress; (v) linking business more effectively with biodiversity and (vi) leveraging the power of international agencies and programmes. Given they are linked to a greater or lesser degree, implementing these six foci together will lead to a much‐needed broadening of the framework, especially those of business and broader urban civil society, as well as those of Indigenous Peoples and Local Communities. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.